Strategy for Improving Service Performance through Organizational Culture and Climate - Kurnaedi, Endang; Agustina, Kania; Karyono, Otong (Budapest International Research and Critics University, 2020)
The problem of competition and the demands of changing times towards globalization and modernization are quite dynamic, so that demands high performance and high performance can be realized by the conducive organizational climate and organizational culture that is open to technological and information changes. This study aims to determine the extent of the role and influence of organizational culture and climate on service performance. This research method uses descriptive and verification research. Descriptive research tries to provide an overview of research variables that are able to provide information on current conditions, while verification research to draw a conclusion to provide an explanation of the relationship between variables, so that by doing verification analysis can provide an explanation of the contribution of the magnitude of the relationship or influence and the results of hypothesis testing that was submitted. The results of the study prove that the organizational culture, organizational climate and service performance variables are descriptive in the good category. While the results of the verification study prove that organizational climate has a greater effect on service performance when compared to organizational culture. The results of this study provide recommendations to the PD. BPR Sukahaji should always maintain, maintain and even improve the creation of climate and organizational culture, especially for the creation of a work environment related to organizational climate.